Survey of relationship between spiritual health and mental health in patients undergoing methadone maintenance treatment (MMT) - abolhassan naghibi; soror ashari; fereshteh rostami; hamze hosseini (Mazandaran University of Medical Sciences, 2015)
Introduction and goal: Religiosity and spirituality decreasesof the impact of life stress on the tendency to substance use. Everyday addedto the number of people who believe that spirituality is the way to treat neuroses and mental problems. This study aimed to determine the relationship between spiritual health and mental health in patients undergoing to methadone maintenance treatment (MMT) dependent on the private and government sector in Sari. Method: This study was cross- sectional study. The target populations of this study were 123 women and men undergoing to methadone maintenance treatment (MMT). The data collected by spiritual and mental health questionnaire and were analyzed using two-sample t-test and spearman correlationin theSPSS (18) software. Findings: The grade average of spiritual health was 43/29 and mental health was 41/26.The results showed that a significant correlation between spiritual health with mental health. The highest correlation was between spiritual healthwith the social function and the lowestcorrelation was with physical problems. There was no significant relationshipbetween of marital status, number of children, sex and spiritual health. Conclusion: According to positive and significant role spiritual health in mental health, so, strengthen the spiritual dimension can to promote mental health and reduce mental disorders and the tendency to addiction.